A survey on the knowledge of breast cancer and adoption of breast self-examination among female undergraduate students of Kulliyyah of Allied Health Sciences, IIUM Kuantan - Saidin, Nursyahirah; Moey, Soo Foon (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2018)
Introduction: Many studies had been carried out on breast cancer awareness and the practice of breast self-examination (BSE). However, few studies had been conducted on the level of knowledge of breast cancer and the adoption of BSE amongst female undergraduate students. Even though, younger women have lower breast cancer incidence but younger women tend to have more aggressive cancer type and possibly present breast cancer at an advance stage. Therefore, it is best to start BSE at an early age especially in the high risk group because it will help in early detection of breast cancer. As such, this study aims to ascertain the level of knowledge of breast cancer and stage of adoption of breast self-examination (BSE) among female undergraduate students of the Kulliyyah of Allied Health Sciences (KAHS), International Islamic University Malaysia (IIUM) Kuantan, Pahang. Methods: A cross-sectional study was carried out on 262 randomly selected female undergraduate students from KAHS, IIUM Kuantan. Data was collected using a validated self-administered questionnaire through a given link. Results: The mean age of the participants was 22.4 years. Approximately 78% of the respondents’ overall knowledge of breast cancer was fair. The knowledge on risk factors for breast cancer among respondents was a mere 48.42%. The majority of the respondents (84%) have heard about BSE. However, only half of the respondents knew how to perform BSE. Further, approximately 60% of respondents were at the pre-contemplation and contemplation stage for adoption of BSE. A significant relationship was found between knowledge of BSE and stage of adoption of BSE. Conclusion: The study found the majority of respondents have a fair knowledge on breast cancer and that knowledge of BSE is related to the stage of adoption of BSE.